BACK ANALYSIS OF LANDSLIDE AT INPIT DUMP AREA OF BERAMBAI COAL MINING, KUTAI KARTANEGARA REGENCY, EAST KALIMANTAN - St Waiyah Andisa, Andi
Insani Bara Perkasa is a significant open-pit mining operation located at Berambai, East Kalimantan, encompassing a total area of 23.668 hectares, divided into several mining blocks. Two of these blocks are known as the Mahakam and Separi Blocks. This research is conducted at inpit dump (IPD) Pit 2 area of Separi Block. This area experienced a continuous landslide during an inpit dump activity in Pit 2. The disposal known can hold as much as 4 Mio LCM of overburden. The consequences of this landslide have been significant, resulting in restricted access to the affected area, and the pit has not reached its final design of the coal mining. In response to this case, a comprehensive study regarding detailed investigation leading to subsequent back analysis to ascertain the root causes of the landslide was conducted. The hyphotesis that causes the landslide are influencing of groundwater. The research methodology employed for the analysis involved the back analysis using the limit equilibrium method. Through iterative of varying scenarios to identify the root causes of the landslide, encompassing combination of distributed load, water level, and seismic, until a safety factor (SF) ?1,0. Based on the research findings, it is imperative to underscore a primary determinant contributing of the landslide are (1) noncircular sliding surface with fully saturated watertable added with load of heavy hauler, and the combination of those two criteria and seismic load. (2) circular sliding surface with fully saturated watertable combined with load of heavy hauler and seismic load. The recommended slope stabilization efforts redesign of the inpint dump geometry with layback and change the slope geometry into height of 37 m with an overall slope of 8° from its initial geometry (height 42 m with an overall slope 10°).